2023
DOI: 10.1111/cob.12585
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients undergoing primary bariatric surgery in the United Kingdom based on the National Bariatric Surgery Registry

Abstract: Summary Baseline demographic characteristics and operations undertaken for patients having bariatric surgery in the United Kingdom are largely unknown. This study aimed to describe the profile of patients having primary bariatric surgery in the National Health Service (NHS) or by self‐pay, and associated operations performed for both pathways. The National Bariatric Surgery Registry dataset for 5 years between January 2015 and December 2019 was used. 34 580 patients underwent primary bariatric surgery, of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…1 B). In terms of primary surgery caseload, in the pre-pandemic period there was a greater proportion of Roux-en-Y gastric bypasses in the NHS than in private settings [ 11 ]. Following the outbreak of the pandemic, changes in primary caseload were most pronounced in the private sector, with a decrease in adjustable gastric bands from 18% to 6% and an increase in SGs from 46% to 53% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 B). In terms of primary surgery caseload, in the pre-pandemic period there was a greater proportion of Roux-en-Y gastric bypasses in the NHS than in private settings [ 11 ]. Following the outbreak of the pandemic, changes in primary caseload were most pronounced in the private sector, with a decrease in adjustable gastric bands from 18% to 6% and an increase in SGs from 46% to 53% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is one of the first studies to comprehensively investigate a range of characteristics associated with receiving NHS bariatric surgery versus not receiving surgery. Bolckmans and colleagues reported that NHS bariatric surgery patients were significantly older and more comorbid than self-paying patients [ 50 ]. We also found that an increasing number of comorbidities was associated with undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that 100% of new staff capacity would be focused on BaS in the scale-up strategy and gastric band surgery would be phased out at a constant rate over the next 10 years, as per input from the bariatric surgeons. 32 …”
Section: Methodsmentioning
confidence: 99%